CGIAR Genebank Platform - Plan of Work and Budget 2021 - CGIAR Genebank Platform (CGIAR Genebank Platform, 2021)
The most important output of the Genebank Platform is the availability and provision of healthy, viable, documented germplasm from the 35 crop and tree collections managed by the CGIAR, which are maintained, and safety duplicated, in long-term conservation in accordance with FAO Genebank Standards (2014) and Article 15 of the International Treaty on Plant Genetic Resources for Food and Agriculture (Plant Treaty). Demand varies unpredictably between years. Figures for germplasm distributions in 2020 are not yet compiled but they are expected to be lower than for a normal year. We expect that the COVID pandemic and associated lockdown measures will have an impact on the number of requests for germplasm that will continue in 2021. Nevertheless, users continue to request germplasm and all 11 genebanks and germplasm health units (GHUs) continue to import and export germplasm shipments. Although requests are being met, the rate of other genebank operations, including those contributing to performance targets, has slowed down, particularly where lockdown measures are more severe in Asia, Europe and Latin America.